Salaiset aseveljet : Suomen ja Saksan turvallisuuspoliisiyhteistyö 1933-1944 - Silvennoinen, Oula (Otava, 2010)
Salaiset aseveljet deals with the relations and co-operation between Finnish and German security police authorities, the Finnish valtiollinen poliisi and the German Reichssicherheitshauptamt (RSHA) and its predecessors. The timeframe for the research stretches from the Nazi seizure of power in 1933 to the end of German-Finnish co-belligerency in 1944. The Finnish Security Police was founded in 1919 to protect the young Finnish Republic from the Communists both in Finland and in Soviet Russia. Professional ties to German colleagues were maintained during the 1920 s, and quickly re-established after the Nazis rose to power in Germany. Typical forms of co-operation concentrated on the fight against both domestic and international Communism, a concern particularly acute in Finland because of her exposed position as a neighbour to the Soviet Union. The common enemy proved to be a powerful unifying concept. During the 1930 s the forms of co-operation developed from regular and routine exchanges of information into personal acquaintancies between the Finnish Security Police top personnel and the highest SS-leadership. The critical period of German-Finnish security police co-operation began in 1941, as Finland joined the German assault on the Soviet Union. Together with the Finnish Security Police, the RSHA set up a previously unknown special unit, the Einsatzkommando Finnland, entrusted with the destruction of the perceived ideological and racial enemies on the northernmost part of the German Eastern Front. Joint actions in northern Finland led also members of the Finnish Security Police to become participants in mass murders of Communists and Jews. Post-war criminal investigations into war crimes cases involving former security police personnel were invariably stymied because of the absence of usually both the suspects and the evidence. In my research I have sought to combine the evidence gathered through an exhaustive study of Finnish Security Police archival material with a wide selection of foreign sources. ...